Capital, endogenous separations, and the business cycle - Björn van Roye; Dennis Wesselbaum (Kiel Institute for the World Economy (IfW), 2009)
We implement capital in an endogenous separations New Keynesian matching model. In contrast to the vintage capital theory, we suggest a more general approach, such that workers have unrestricted access to a proportional share of the capital stock. We find that the introduction of capital generates an important channel for the transmission of aggregate productivity shocks, using capital-labor trade-off. The model generates higher volatilities of key variables and therefore enhances the performance of the matching model to generate stylized facts in response to an aggregate productivity shock. However, there is almost no difference for monetary policy shocks.
Keywords: E22; E32; J64; 330; Capital; Endogenous Separations; Search and Matching